Tax Aggressiveness and Audit Report Timeliness: The Role of Ownership Structure and Audit Committee - Vionna Lievia; Antonius Herusetya (Indonesian Journal of Sustainability Accounting and Management, 2022)
Companies that engage in tax aggressiveness (TAG) are considered socially irresponsible and problematic from the perspective of tax authorities. This study examines the impact of TAG on audit report timeliness and the role of corporate governance using ownership structure and audit committee on the relationship between TAG and audit report timeliness. We use the tax planning prediction model to uncover TAG. The data for our sample is obtained from the manufacturing companies listed on the Indonesia Stock Exchange and was obtained using the purposive sampling method. Using multiple linear regression analysis, we discover a positive relationship between TAG and audit report timeliness. However, we also find that corporate governance mechanisms affect this positive relationship through ownership structure and audit committee competence. Our findings suggest that the delay of independent auditors due to audit processes may expose the activities of TAG’s clients, which may have economic consequences for tax authorities, companies, and other stakeholders.